Religion, Clothing and Modernity (The Influence of Elzatta and Rabbani on the Development of Indonesian Muslim Fashion) - Abdul Manan; Siti Munawati (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The development of Muslim fashion trends plays a role that is always in demand by various Indonesian people as a symbol of the identity of a modern lifestyle. Today's fashion trends not only include casual wear but also permeate Muslim fashion styles, especially the hijab. The modernization of the Muslim clothing industry is currently growing rapidly, even Muslim women's clothing has become a separate trend in Indonesian people's clothing. The development of Muslim clothing proves that modernization is inevitable and includes the lifestyle of a country. Clothing as the latest cultural phenomenon is a manifestation of human needs and has artistic-entrepreneurial value, which has respect, beauty, and strength. In addition, there is a selling point in the context of the success of marketing, and advertising that appeals to consumer desires and has a symbol of social recognition. The existence of Elzatta and Rabbani consistently, their contribution and role is quite large, it is proven by always upholding Islam. A profession that requires hijab users to always know the development of Muslim fashion, and must be active and creative in finding out to create hijab trends with attractive clothing. This makes the designers of the two industries an icon that represents hijab fashion in Indonesia. The method used in this research is qualitative research with a case study approach and data collection methods through two primary and secondary data, with interviews, observations to Elzatta and Rabbani, as well as documentation from libraries, journals and others. By using social change theory, modernization theory, and lifestyle theory. The results showed that the existence of modern Muslim clothing as a religious identity in the fulfillment of the Islamic creed but became a fashion trend that only refers to the covering of aurat. As for the identity of the wearer, the clothing creates a new identity for the wearer, which is no longer a religious identity but rather an identity of modernity and popularity, namely wearing the hijab with a modern style in addition to wanting to look more fashionable and following trends. As owners of hijab products, Elzatta and Rabbani have the orientation of the hijab command to develop innovations from the latest creative lifestyle ideas and produce hijab and clothing products that can be accepted by the market.